RIPK3‐mediated cell death is involved in DUX4‐mediated toxicity in facioscapulohumeral dystrophy. Issue 6 (22nd October 2021) - Mariot, Virginie; Joubert, Romain; Le Gall, Laura; Sidlauskaite, Eva; Hourde, Christophe; Duddy, William; Voit, Thomas; Bencze, Maximilien; Dumonceaux, Julie
Abstract: Background: Facioscapulohumeral dystrophy (FSHD) is caused by mutations leading to the aberrant expression of the DUX4 transcription factor in muscles. DUX4 was proposed to induce cell death, but the involvement of different death pathways is still discussed. A possible pro‐apoptotic role of DUX4 was proposed, but as FSHD muscles are characterized by necrosis and inflammatory infiltrates, non‐apoptotic pathways may be also involved. Methods: We explored DUX4‐mediated cell death by focusing on the role of one regulated necrosis pathway called necroptosis, which is regulated by RIPK3. We investigated the effect of necroptosis on cell death in vitro and in vivo experiments using RIPK3 inhibitors and a RIPK3‐deficient transgenic mouse model. Results: We showed in vitro that DUX4 expression causes a caspase‐independent and RIPK3‐mediated cell death in both myoblasts and myotubes. In vivo, RIPK3 ‐deficient animals present improved body and muscle weights, a reduction of the aberrant activation of the DUX4 network genes, and an improvement of muscle histology. Conclusions: These results provide evidence for a role of RIPK3 in DUX4‐mediated cell death and open new avenues of research.